Conclusions of the Task Force on IMF Technical Assistance. (Policy Papers; Policy Paper ;, 2005)
Task Force proposals include: (i) preparation, on a pilot basis, of five TA country strategy notes in FY 2006 and, based on a positive assessment of the pilot, extension of the country coverage to possibly 50 countries in FY2007; (ii) enhanced strategic and monitoring role in TA for area department staff, including resident representatives; (iii) enhancements to the central TA information system under its ongoing Phase II; (iv) more systematic involvement of country authorities in the design and implementation of the TA they receive; and (v) more systematic discussion of technical options and their implications with the authorities before drafting TA reports.